2010
DOI: 10.1002/cbic.201000349
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Activity‐Based Probe for Autotaxin

Abstract: Autotaxin (ATX), or ecto-nucleotide pyrophosphatase/phosphodiesterase 2 (ENPP2), is a secreted lysophospholipase D that hydrolyses lysophosphatidylcholine into the lipid mediator lysophosphatidic acid (LPA), a mitogen and chemoattractant for many cell types. ATX has been implicated in tumour progression and inflammation, and might serve as a biomarker. Here we describe the development of a fluorescent activity-based probe that covalently binds to the active site of ATX. The probe consists of a lysophospholipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…As observed in the choline release assay, activation by 18:1 LPA resulted in an AC 50 value of 1.1 ± 0.3 µM (Fig.4D). Consistently, pre-incubating ATX with LPA for 30 minutes before supplying the LPC substrate reduced the length of the lag phase (Fig.4E-F).Taken together, these assays point out to two separate LPA sites: an orthosteric high affinity (~50 nM) site, virtually identical to the primary LPC binding site that leads to catalysis or competition with minimal inhibitors and has been well characterized (22,23,33); and an allosteric low affinity (~1.5 µM) site that leads to an activation of LPC hydrolysis. These observations are of key importance to start understanding the lag phase we described above.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…As observed in the choline release assay, activation by 18:1 LPA resulted in an AC 50 value of 1.1 ± 0.3 µM (Fig.4D). Consistently, pre-incubating ATX with LPA for 30 minutes before supplying the LPC substrate reduced the length of the lag phase (Fig.4E-F).Taken together, these assays point out to two separate LPA sites: an orthosteric high affinity (~50 nM) site, virtually identical to the primary LPC binding site that leads to catalysis or competition with minimal inhibitors and has been well characterized (22,23,33); and an allosteric low affinity (~1.5 µM) site that leads to an activation of LPC hydrolysis. These observations are of key importance to start understanding the lag phase we described above.…”
supporting
confidence: 68%
“…Taken together, these assays point out to two separate LPA sites: an orthosteric high affinity (~50 nM) site, virtually identical to the primary LPC binding site that leads to catalysis or competition with minimal inhibitors and has been well characterized (22,23,33); and an allosteric low affinity (~1.5 µM) site that leads to an activation of LPC hydrolysis. These observations are of key importance to start understanding the lag phase we described above.…”
Section: Lpa Modulates Atx Catalysismentioning
confidence: 99%
“…Therefore, the exploring of ATX inhibitors is highly focused in cancer therapy, and several ATX specific inhibitors have been developed in recent years [43-45]. In the present paper, we have demonstrated that inhibition of ATX lysoPLD activity with ATX inhibitor (such as BrP-LPA and S32826) could enhance the TSA-induced apoptosis in cancer cells.…”
Section: Discussionmentioning
confidence: 57%
“…http://dx.doi.org/10.1101/346288 doi: bioRxiv preprint first posted online Jun. 13, 2018; Taken together, these assays point out to two separate LPA sites: an orthosteric high affinity (~50nM) site, virtually identical to the primary LPC binding site that leads to catalysis or competition with minimal inhibitors and has been well characterized 25,26,34 ; and an allosteric low affinity (~1.5 µM) site that leads to an activation of LPC hydrolysis. These observations are of key importance to start understanding the lag phase we described above.…”
Section: Resultsmentioning
confidence: 99%